Vectorial Control (FOC) of Induction Motor using DSP - Soto Lock, Alberto (2005)
In this paper, it is show fundamentals of Field Oriented Control FOC, it is show also how Digital Signal Processors DSP can handle the problem of controlling Induction Motors IM in order to obtain a high performance